2008
DOI: 10.1017/s0022112007009962
|View full text |Cite
|
Sign up to set email alerts
|

The elephant mode between two rotating disks

Abstract: Spectral direct numerical simulations (DNS) are carried out for a source-sink flow in an annular cavity between two co-rotating disks. When the Reynolds number based on the forced inflow is increased, a self-sustained crossflow instability of finite amplitude is observed. We show that this nonlinear global mode is made up of a front located at the upstream boundary of the absolutely unstable domain, followed by a saturated spiral mode, and that its properties are in good agreement with results of the local sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…Although the local absolute instability only exists above R CA , as observed in the numerical study between two rotating disks (i.e. in an open rotating cavity) by Viaud, Serre & Chomaz (2008), the global mode is expected to connect smoothly to the upstream convectively unstable region, giving a nonlinear front straddling R CA . Therefore, as expected, the profile of the travelling disturbance at R = 490 indicates the upstream matching between travelling convectively and absolutely unstable regions.…”
Section: Comparisons Of Velocity-disturbance Spectramentioning
confidence: 81%
“…Although the local absolute instability only exists above R CA , as observed in the numerical study between two rotating disks (i.e. in an open rotating cavity) by Viaud, Serre & Chomaz (2008), the global mode is expected to connect smoothly to the upstream convectively unstable region, giving a nonlinear front straddling R CA . Therefore, as expected, the profile of the travelling disturbance at R = 490 indicates the upstream matching between travelling convectively and absolutely unstable regions.…”
Section: Comparisons Of Velocity-disturbance Spectramentioning
confidence: 81%
“…Nevertheless, our simulations now confirm that the rotating-disk boundary layer can produce a linear amplified global mode. It would be interesting to investigate whether the rotating cavity simulated by Viaud, Serre & Chomaz (2008), for example, can be shown to become globally linearly unstable by moving the edge radially outwards, allowing the disturbances to grow, saturate and produce turbulence prior to the end of their domain.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the subject can be found in Owen & Rogers (1995). The recent numerical work by Viaud, Serre & Chomaz (2008) (from now on labelled VSC) has demonstrated the similarity of the local velocity profiles in the boundary layers over a single rotating disc and in an annular rotating cavity with a forced throughflow. For the cavity, VSC have shown that the flow is linearly stable but nonlinearly unstable with large initial perturbation giving rise to self-sustained nonlinear global mode with a steep front located at the transition point between convective and absolute instability (the so-called elephant mode).…”
Section: Introductionmentioning
confidence: 95%